2016
DOI: 10.1002/jbmr.2792
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Murine Fgf23: Interruption of the Normal Skeletal Responses to Phosphate Challenge and Rescue of Genetic Hypophosphatemia

Abstract: The transgenic and knock out (KO) animals involving Fgf23 have been highly informative in defining novel aspects of mineral metabolism, but are limited by shortened life span, inability of spatial/temporal FGF23 control, and infertility of the global KO. To more finely test the role of systemic and genetic influences in FGF23 production, a mouse was developed that carried a floxed (‘f’)-Fgf23 allele (exon 2 floxed) which demonstrated in vivo recombination when bred to global-Cre transgenic mice (eIIa-cre). Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 67 publications
2
55
0
1
Order By: Relevance
“…The amount of non-mineralized bone was significantly reduced in the treated mice and approached WT levels in the Hyp mice receiving high dose anti-FGF23. These data, in conjunction with bone specific flox- Fgf23 knockout studies in Hyp mice (21), demonstrated the key driver of the hypophosphatemia phenotype is FGF23 and therefore validates the anti-FGF23 antibody treatment regimen.…”
Section: Novel Therapies Based Upon Clinical and Genetic Discoveriessupporting
confidence: 55%
See 1 more Smart Citation
“…The amount of non-mineralized bone was significantly reduced in the treated mice and approached WT levels in the Hyp mice receiving high dose anti-FGF23. These data, in conjunction with bone specific flox- Fgf23 knockout studies in Hyp mice (21), demonstrated the key driver of the hypophosphatemia phenotype is FGF23 and therefore validates the anti-FGF23 antibody treatment regimen.…”
Section: Novel Therapies Based Upon Clinical and Genetic Discoveriessupporting
confidence: 55%
“…These various forms of FGF23 can be detected in the circulation using FGF23 specific enzyme-linked immunosorbent assays (ELISAs) for humans and rodents (Kainos, Inc (20) and Qidel, Inc (21)). Intact FGF23 measurements utilize two antibodies that bind at both the N - and C -terminal portions of the full-length, bioactive form of the hormone (or ‘iFGF23’).…”
Section: Heritable Disorders Of Hypophosphatemia Involving Fgf23mentioning
confidence: 99%
“…Although other tissues may also contribute to circulating intact FGF23 concentrations [6], bone is probably the major source for circulating FGF23 under physiological circumstances in vivo [5]. There is good evidence that FGF23 is secreted by both osteocytes and osteoblasts in bone [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Primary cultures of osteoblastic cells from Hyp mice also fail to properly mineralize, thus underscoring an intrinsic cellular defect due to only partially resolved mechanisms (Bai et al, 2004). FGF23 is central to the Hyp metabolic bone disease phenotype, as demonstrated by the fact that global (Sitara et al, 2004) or osteoblast-specific (Clinkenbeard et al, 2016) knockout of Fgf23 in the Hyp genetic background reverses, or rescues, respectively, the low serum phosphate phenotype. However the molecular mechanisms controlling FGF23 in Hyp remain unknown.…”
Section: Introductionmentioning
confidence: 99%